Limosilactobacillus reuteri regulates gut microbiota and increases the effective metabolite luteolin to inhibit MAPK/STAT3 signaling pathway to alleviate allergic rhinitis - Zhang, Mingyan; Sun, Xuewei; Yu, Xiang; Xu, Li; Zhang, Xinrui; Zhang, Ruonan; Lu, Han; Wang, Yujie; Xue, Fei; Zhang, Ting; Tang, Chengliang; Wu, Zihan; et al. (Frontiers in Microbiology, 2025)
The global prevalence of allergic rhinitis (AR) remains high, posing challenges due to its chronic nature and propensity for recurrence. Gut microbiota dysbiosis contributes to immune dysregulation, impacting AR pathogenesis. Limosilactobacillus reuteri (L. reuteri) has great potential in regulating immune function to alleviate AR symptoms. However, the specific active components and mechanisms underlying its therapeutic effects in AR remain incompletely clarified. This study aimed to explore the potential mechanisms of L. reuteri and its metabolites in alleviating AR. The AR mouse model was constructed using ovalbumin (OVA). The analysis of hematoxylin–eosin staining (HE staining) and enzyme-linked immunosorbent assay (ELISA) suggested that L. reuteri alleviated nasal inflammation, suppressed aberrant Th2 immune responses, and modulated the balance of Treg and Th17 cytokines. The 16S rRNA sequencing and untargeted metabolic analysis revealed that L. reuteri restored gut microbiota composition and significantly increased the abundance of Ligilactobacillus and the metabolite luteolin (LO). Through ELISA and Western blotting analysis, LO treatment restored the Th1/Th2 and Treg/Th17 cytokine balance and suppressed the MAPK/STAT3 signaling pathway in AR mice. The study highlights LO as a key metabolite contributing to the anti-inflammatory effects of L. reuteri, suggesting potential avenues for future therapeutic strategies in AR management.